Comparison of on-ice and off-ice graded exercise testing in collegiate hockey players - Durocher, J. J.; Guisfredi, A. J.; Leetun, D. T.; Carter, J. R. (Applied Physiology, Nutrition, and Metabolism, 2010)
The purpose of this study was to compare lactate thresholds (LT) and maximal aerobic capacities (VO2 max symbol does not display correctly in the abstract online, so was changed to an italic V. It appears correctly in the body of the paper.) during sport-specific skating (on ice) and cycle ergometry (off ice) in collegiate hockey players. We hypothesized that VO2 max and LT would be higher on ice. We also sought to determine if on-ice and off-ice VO2 max values were correlated. Twelve collegiate hockey players performed both graded exercise protocols in randomized order to fatigue. Both protocols included 80 s of work during each stage, followed by 40 s of rest to allow for blood lactate sampling. VO2 max was significantly higher on ice (46.9 ± 1.0 mL/kg·min) than off ice (43.6 ± 0.9 mL/kg·min; p < 0.05). Maximal heart rate (HRmax) was also higher on ice (192.2 ± 1.8 beats/min) than off ice (186.0 ± 1.5 beats/min; p < 0.01). LT was drastically higher on ice than off ice as a percentage of VO2 max (85.9% ± 1.9% vs. 69.7% ± 1.3%; p < 0.01) and HRmax (90.1% ± 1.3% vs. 79.4% ± 1.6%; p < 0.01). Finally, no correlation existed between VO2 max values off ice and on ice (r = -0.002; p = 0.99). Our results indicate that off-ice VO2 max and LT are not adequate predictors of on-ice VO2 max and LT in collegiate hockey players. These findings challenge the use of cycle ergometry to assess aerobic capacity at events such as the National Hockey League Entry Draft combine. We suggest that hockey players be tested in a sport-specific manner, regardless of whether those tests are performed on ice or off ice.